Derivation of Shadow Prices for Undesirable Outputs: A Distance Function Approach - Fare, Rolf; Grosskopf, Shawna; Lovell, C. A. Knox; Yaisawarng, Suthathip (The Review of Economics and Statistics, 1993)
, Shawna Grosskopf, C. A. Knox Lovell, Suthathip Yaisawarng, Derivation of Shadow Prices for Undesirable Outputs: A Distance Function Approach, The Review of Economics and Statistics, Vol. 75, No. 2 (May, 1993), pp. 374-380